Fostering Independent Character Education: Insights from Elementary School Context: Memupuk Pendidikan Karakter Mandiri: Wawasan dari Konteks Sekolah Dasar - Amalia, Rizky; Wachidah, Kemil (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative case study research investigates the implementation of an independent character education strengthening program at an elementary school. Focused on Class V-A students, teachers, and the principal at the school, the study employs interviews, observations, and documentation for data collection, with triangulation for data validity. Utilizing Miles and Huberman's techniques for analysis, the research highlights the significance of independent character education for the school community, evident through indicators, subject matter integration, and school culture. The study underscores the importance of fostering independent character education and its positive impact on students and school stakeholders. Highlights: Implementation Insights: Investigating the application of an independent character education strengthening program. Stakeholder Perspective: Examining the viewpoints of Class V-A students, teachers, and the principal. Integral Elements: Showcasing the integration of subject matter and school culture in fostering independent character education. Keywords: Character education, Strengthening program, Elementary school, Qualitative research, School culture